Continued Substance Use Among People Living With HIV–Hepatitis-C Co-Infection and Receiving Antiretroviral Therapy. (15th October 2015) - Kalichman, Seth C.; Washington, Christopher; Kegler, Christopher; Grebler, Tamar; Kalichman, Moira O.; Cherry, Chauncey; Eaton, Lisa
Abstract : Background : Co-infection with human immunodeficiency virus (HIV) and Hepatitis-C virus (HCV) poses a significant threat to personal and public health. Substance use among co-infected persons leads to increased morbidity and mortality. The purpose of this study is to examine the continued substance use of people living with HIV–HCV co-infection and receiving antiretroviral therapy (ART). Methods : Individuals living with HIV infection in Atlanta, GA and currently receiving ART ( N = 678) completed audio-computer-assisted self-interviews for demographic, health, and behavior characteristics; unannounced pill counts to assess ART adherence over one month; finger-stick blood specimens collected for HCV antibody testing and urine specimens for drug use screening; and obtained HIV viral load and CD4 cell counts from their medical provider. We performed cross-sectional analyses for behavioral and biological markers of health, health behaviors, and substance use. Results : Among participants, 131 (19%) were HIV–HCV co-infected; 53% were HIV-mono-infected, and 60% of HIV–HCV co-infected participants tested positive for use of at least one non-alcohol drug: tetrahydrocannabinol (THC) and cocaine were most prevalent. HIV–HCV co-infected individuals were older, with no other significant differences. Within the HIV–HCV co-infected participants, drug users ( N = 87) did not differ from non-drug users ( N = 53) in terms of ART adherence. However, drug users were significantly more likely to have uncontrolled HIV (17%) compared with those who did not test drug positive (4%). Conclusions : Substance use is prevalent in persons with HIV–HCV co-infection and may interfere with ART. Research with a larger and more representative sample is needed to replicate and confirm these results.